صورة الطبيب لدى المجتمع العراقي (دراسة ميدانية في مدينة الكوت) - البعاج, هديل تومان محمد مهدي (lark, 2019)
The mental image considered individual or collective imagination about something certain; it became the image to the meaning in which the brain could call for as soon as such thing comes to the mind. Mental image considered as composite of rules, impression and imagination. The research handles the image of the doctor which is in Iraqi citizen mind that has gone through changes several recently. The first study of the research handled the research methodology while the second and third study of the research handled the theoretical side of identifying the concept of the image of mind and how to configure the concept of a doctor, while the fourth study handled the field study which it turns out of which the formed image at the citizen towards the doctor. The researcher has made use of field survey approach using each of the tools (resolution and scale) to explore and clarify the outcomes the field study. It has been shown by the results that the image of the Iraqi doctor is a negative image that the majority of the results demonstrate that the medical profession has become a Profession to make and exploiting money